Passing Through Shanghai: Ethnographic Insights into the Mobile Lives of Expatriate Youths - Sander, Marie (Heidelberg Studies on Transculturality, 2016)
Passing Through Shanghai examines how children experience international mobility. Focusing on a specific yet diverse group of expatriate youths in contemporary Shanghai, the book investigates how children negotiate cultural identity when they are subject to the highly mobile and often privileged lifestyle associated with their parent's international careers. The ethnographic fieldwork that informs the book was carried out in Shanghai from 2010 to 2012 and focused on expatriate teenagers' everyday practices, their lives at international schools, their engagement with the city, their dreams and aspirations, as well as their questions of belonging. The book's ethnographic approach captures the "in-between" state of moving while growing up and explores teenage practices and positionings in this transitory situation. The teenagers' own perspectives and experiences of living in expatriate communities contribute to a larger view of the interdependence and contradictions between the aspired flexibility of twenty-first century identities and the rigidity of cultural divisions based on nationality, ethnicity, gender, and class.